GENDER STEREOTYPE ROLE IN THE BUSINESS SUCCESS OF WOMEN ENTREPRENEURS IN INDONESIA - Hendry Hartono; Wella Luhur; Sasmoko Sasmoko; Nugroho Juli Setiadi; Abdul Aziz Abdulah (International Journal of Organizational Business Excellence, 2019)
Having good business relationships with stakeholders and have innovative behaviours that are competitive, full of challenges, as well as risks to achieve success in the business.In relationships and behaviours, human beings are inseparable from their views on the attributes or characteristics of women and that have to be performed by women and men who are subconsciously embedded and absorbed in each individual's subconscious, which is commonly referred to as gender stereotypes.This is notapart from its influences on business relationships and innovative behaviours of women entrepreneurs in their business to achieve business success.It is interesting to examine whether gender stereotypes are moderate business relationships and innovative behaviours towards the success of women entrepreneur business in Indonesia.Sources of data obtained by distributing questionnaires and interviewing 109 women entrepreneurs.This research is a quantitative research using the Hierarchical Regression Analysis research method.The findings of this study show that women are more likely to have a relationship with women entrepreneurs.Gender stereotype as a moderating variable does not affect business relationships with a moderate relationship between innovativebehaviour towards business success in women entrepreneurs in Indonesia, and the result shows gender stereotype decrease the influence of innovative behaviours of women entrepreneurs to the success of their business.